SHM_99564_HST_3D Simple Shaft-Hole Stone Axe - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a simple stone shaft-hole axe from the Swedish Late Neolithic or Early Bronze Age, collected in the field from Hol Bryngelsgården in Västra Götaland and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=406

Link to Sök I Samlingarna

https://samlingar.shm.se/object/147AE4AB-3221-49A5-A0DA-82AB7E2D8A9C?type=object&query=99564_HST&n=1
Keywords: Archaeology; Archaeology; Archaeology/history; Structured Light Scanning; 3D Model; Museum Object; Dynamic Collections; Hol Bryngelsgården; Swedish Late Neolithic; Swedish Early Bronze Age; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi